Multidimensional incongruence, political disaffection, and support for anti-establishment parties. Issue 2 (1st February 2020) - Bakker, Ryan; Jolly, Seth; Polk, Jonathan
ABSTRACT: To what extent do representational gaps between parties and voters destabilise party systems and create electoral opportunities for anti-establishment parties on the left and right? In this paper, we use multiple measures of party-partisan incongruence to evaluate whether issue-level incongruence contributes to an increase of political disaffection and anti-establishment politics. For this analysis, we use data from the Chapel Hill Expert Survey (CHES) for party positions and public opinion data from the European Election Study (EES). Our findings indicate that multidimensional incongruence is associated with disaffection at the national and European level, and that disaffected mainstream party voters are in turn more likely to consider voting for anti-establishment challenger parties. This finding suggests that perceived gaps in party-citizen substantive representation have important electoral ramifications across European democracies.